1997
DOI: 10.1515/comm.1997.22.1.5
|View full text |Cite
|
Sign up to set email alerts
|

The Rediscovery of Opinion Leaders. An Application of the Personality Strength Scale

Abstract: Opinion leadership has been the subject of numerous studies, in areas ranging from politics to marketing. The present study examines a new measure to identify opinion leaders (the personality strength scale developed by the Aliensbach Survey Center in Germany) and combines it with modern social network analysis. An application of this scale to agenda setting and public opinion research is the main point of concern in this study. The findings of the study (a survey of a representative sample of 900 adults in Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 5 publications
0
8
0
5
Order By: Relevance
“…Die als persönlichkeitsstark ermittelten Befragten verfügten über einen größe-ren Bekanntenkreis, der auch Personengruppen mit anderen Merkmalen als den eigenen (z.B. anderes Alter, anderer Sozialstatus) umfasste (Schenk 1995;Schenk & Rössler 1997). Dabei waren sie selbst tendenziell in höheren sozialen Schichten zu finden -weshalb die Skala der Persönlichkeitsstärke doch auch Aussagen über den sozialen Status erlaubte (vgl.…”
Section: 7unclassified
See 2 more Smart Citations
“…Die als persönlichkeitsstark ermittelten Befragten verfügten über einen größe-ren Bekanntenkreis, der auch Personengruppen mit anderen Merkmalen als den eigenen (z.B. anderes Alter, anderer Sozialstatus) umfasste (Schenk 1995;Schenk & Rössler 1997). Dabei waren sie selbst tendenziell in höheren sozialen Schichten zu finden -weshalb die Skala der Persönlichkeitsstärke doch auch Aussagen über den sozialen Status erlaubte (vgl.…”
Section: 7unclassified
“…Sie verfügten über einen größeren Interessenshorizont und hatten ein divergentes Mediennutzungsverhalten; sie konsumierten v.a informationsreiche Medien intensiver und genauer (Weimann 1992). Das überdurchschnittliche Informationsverhalten ging mit einem ausgeprägten Wissen über eine Vielzahl öffentlicher Themen einher (Schenk & Rössler 1997). Dabei konnten die Persönlichkeitsstarken die öffentliche Meinung recht gut einschätzen, vertraten aber auch eigene Positionen, die teilweise von der Mehrheitsmeinung abwichen.…”
Section: Kernsätzeunclassified
See 1 more Smart Citation
“…Consumers with high personality strength achieve higher levels of satisfaction in life and are generally more integrated into their communities (Scheufele, 1999). Personality strength is positively related to a person's engagement in social activities, and it has been shown that people with high personality strength engage in larger social networks and talk to others more often (Schenk and Rö ssler, 1997). Due to their larger networks and integration into larger communities, consumers with high personality strength frequently meet new people, speak at meetings, participate actively in discussions, and take part in social events (Weimann, 1994;Noelle-Neumann, 1985).…”
Section: Social Leadershipmentioning
confidence: 99%
“…Some of the applied contexts where opinion leadership has been studied include fashion (Baumgarten, 1975), healthcare decisions (Kravitz et al, 2003), the diffusion of prescribed drugs advice (Albertson, 2004), consumer products (Myers & Robertson, 1972;King & Summers, 1970;Chan & Misra, 1990), automobile purchase behavior (Richins & Root-Shaffer, 1988), cable television usage (Childers, 1986), political behavior (Schenk & Rossler, 1997), agricultural technologies (Marsh & Coleman, 1956;Rogers, 2003), forestry management (Haymond, 1988) and soil conservation (Korsching & Hoban, 1990). In general, these studies focused on indentifying the characteristics of opinion leaders and finding positive correlations between social activity, knowledge about, and involvement with the innovation of interest and the likelihood of influencing others' attitudes and/or behaviors concerning the innovation involved.…”
Section: Defining Opinion Leadershipmentioning
confidence: 99%